Retina dose as a predictor for visual acuity loss in 106Ru eye plaque brachytherapy of uveal melanomas. Issue 3 (June 2018) - Heilemann, Gerd; Fetty, Lukas; Blaickner, Matthias; Nesvacil, Nicole; Zehetmayer, Martin; Georg, Dietmar; Dunavoelgyi, Roman
Abstract: Background and purpose: To evaluate the retina dose as a risk factor associated with loss of visual acuity (VA) in 106 Ru plaque brachytherapy. Material/methods: 45 patients receiving 106 Ru plaques brachytherapy (median follow-up 29.5 months) were included in this study. An in-house developed treatment planning system with Monte Carlo based dose calculation was used to perform treatment planning and dose calculation. Risk factors associated with loss of VA were evaluated using the Cox proportional hazards models, Kaplan–Meier estimates and Pearson correlation coefficients. Results: A significant correlation was found between VA loss and mean ( r  = 0.49, p  = 0.001) and near maximum ( r  = 0.47, p  = 0.001) retina dose D2% and tumor basal diameter ( r  = 0.50, p  < 0.001). The Kaplan–Meier and Cox proportional hazards model yielded a significantly higher risk for VA loss (>0.3 Snellen) for patients receiving a maximum dose of >500 Gy ( p  = 0.002). A Cox multivariate analysis including the macula dose ( p  = 0.237) and basal diameter ( p  = 0.791) showed that a high maximum retinal dose is the best risk factor ( p  = 0.013) for VA loss. Conclusion: The study showed that retina dose (D2% and Dmean ) is a suitable predictor for VA loss.